2018
DOI: 10.3390/jmse6040148
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Tsunami Wave Impact and Associated Connection Forces in Open-Girder Coastal Bridges

Abstract: In view of the widespread damage to coastal bridges during recent tsunamis (2004 Indian Ocean and 2011 in Japan) large-scale hydrodynamic experiments of tsunami wave impact on a bridge with open girders were conducted in the Large Wave Flume at Oregon State University. The main objective was to decipher the tsunami overtopping process and associated demand on the bridge and its structural components. As described in this paper, a comprehensive analysis of the experimental data revealed that: (a) tsunami bores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 21 publications
0
38
0
1
Order By: Relevance
“…The two load cells installed on the shear keys and the two on the substructure link measured the horizontal forces at two different levels, while the eight load cells below the bearings and the six load cells below the bent cap measured the vertical forces in bearings and columns, respectively. Using the measured forces, the wave-induced moment was calculated as shown in [28]. Figure 3 shows the time-histories of recorded vertical and horizontal forces, together with the calculated moments, for three selected solitary waves and three bores.…”
Section: Instrumentation and Calculated Quantitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The two load cells installed on the shear keys and the two on the substructure link measured the horizontal forces at two different levels, while the eight load cells below the bearings and the six load cells below the bent cap measured the vertical forces in bearings and columns, respectively. Using the measured forces, the wave-induced moment was calculated as shown in [28]. Figure 3 shows the time-histories of recorded vertical and horizontal forces, together with the calculated moments, for three selected solitary waves and three bores.…”
Section: Instrumentation and Calculated Quantitiesmentioning
confidence: 99%
“…These large OTMs have also been observed in previous studies (e.g., [11,15,17]) but their temporal variation and effect on the structural components has not yet been fully understood. A detailed discussion of the role of OTM for bridge decks with steel bearings is presented in [28].…”
Section: Instrumentation and Calculated Quantitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that two different waves result in different flow hydrodynamics, i.e., wave height and flow velocity. Istrati et al [18] investigated the different types of tsunamis, i.e., solitary waves and bores, and their effect on I-grider bridge with cross-frames. They characterized the induced forces from a bore as short-duration impulsive horizontal force at the time of bore impact that is followed by a smaller magnitude and longer duration forces.…”
Section: Introductionmentioning
confidence: 99%